Methods of test for orthoboric acid (boric acid), diboron trioxide (boric oxide), disodium tetraborates, sodium perborates and crude sodium borates for industrial use. Determination of total aluminium content of crude sodium borates Part 11, (28th February 1979) - British Standards Institution,
No abstract available